Kedudukan Bank Indonesia Dalam Kepailitan Bank - M. Fauzi (Fakultas Hukum Universitas Mulawarman, 2009)
In pursuant to the Pasal 2 ayat (3) UU Kepailitan, the position of Bank Indonesia in the banking bankruptcy will be as banking authority rather than as banking creditor. The determination of Bank Indonesia as the only party to submit the bankruptcy proposal over the bankrupt bank should not comply with generally accepted bankruptcy principles, aimed to give rights and protections for creditor interest. Therefore, the adjustment of legal construction of banking bankruptcy to the bankruptcy legal principles must be considered to realize the objective and the function of bankruptcy agency, and to protect the creditor rights. The objective and function of bankruptcy agency to protect creditor interest from the bankrupt bank can smoothly be ensured to stabilize banking in general.